Community Empowerment through Legal Education on the Legal Impact of Early Marriage - Chairus Suryati; Leni Indrayani (Outline Publisher, 2024)
Early marriage is a social issue that has a negative impact on the health, psychology, and future of the children involved. In Indonesia, the prevalence of early marriage is still quite high, especially in areas with low levels of education and legal awareness. This study aims to provide legal education to the community regarding the legal impact of early marriage and the importance of prevention through community empowerment. Through legal counseling involving community leaders, educational institutions, and local governments, it is hoped that the community can understand the legal consequences of early marriage, both in terms of laws and regulations and children's rights. The results of this education show an increase in public knowledge about early marriage, as well as an awareness of the importance of protecting children, especially related to their rights protected by Law Number 16 of 2019 concerning Marriage. This legal education program is expected to reduce the number of early marriages and encourage better social change in society, especially in realizing healthy, prosperous, and harmonious families. Community empowerment through legal education is an important step in creating sustainable social change and increasing legal awareness among the wider community.